Transformasi Digital dan Technopreneurship pada Usaha Breeding Burung Paruh Bengkok melalui Pemanfaatan Media Sosial ( Studi Kasus Goes Aya Parrot, Bandung) - Diana Effendi; Eddy Soeryanto Soegoto; Tri Utomo Wiganarto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Digital transformation has become a key strategy for small businesses to expand their markets, build customer trust, and enhance competitiveness. This study aims to analyze the form of digital transformation at the Goes Aya Parrot curved-beak bird breeding business through the use of social media, identify the role of each digital platform, and explain how these practices represent a technopreneurship strategy. This study employs a qualitative approach with a descriptive case study design. Data were collected through semi-structured interviews with the business owner and documentation of Facebook, Instagram, and TikTok accounts. The results indicate that digital transformation occurs gradually, beginning with the use of Facebook as a digital portfolio, then expanding to Instagram and TikTok in alignment with the characteristics of each platform’s audience. Social media is utilized not only as a promotional tool but also as a means of building trust, a platform for customer interaction, and an instrument for market expansion. These findings indicate that the use of social media at Goes Aya Parrot constitutes a form of digital transformation for small businesses that simultaneously embodies a technopreneurship strategy.